The perfectionism of Nussbaum's adaptive preferences - Terlazzo, Rosa E. (My University, 2014)
Although the problem of adaptiveness plays an important motivating role in her work on human capabilities, Martha Nussbaum never gives a clear account of the controversial concept of adaptive preferences on which she relies. In this paper I aim both to reconstruct the most plausible account of the concept that may be attributed to Nussbaum, and to provide a critical appraisal of that account. Although her broader work on the capabilities approach moves progressively towards political liberalism as time passes, I aim to show that her account of adaptive preferences continues to maintain her earlier commitment to perfectionism about the good. I then distinguish between two obligatory kinds of respect for persons, which I call respectively primary and secondary recognition respect. This distinction allows us to see that that her perfectionist account of adaptive preferences allows her to show persons primary but not secondary recognition respect. Ultimately, I claim that an acceptable account of adaptive preferences must succeed in showing persons both types of respect. I conclude with some preliminary remarks on what such an account might look like.
Keywords: Adaptive preference; Perfectionism; Nussbaum; Political liberalism; Respect